Public perceptions of threats from mosquitoes in the U.S. using online media analytics. (2nd January 2021) - Widmar, Nicole J. Olynk; Bir, Courtney; Long, Evan; Ruple, Audrey
ABSTRACT: Mosquito-borne illnesses present a public health threat. This analysis quantifies general online mosquito media, and the Zika virus [ZIKV) specifically, from 7–20-2016 to 10–20-2018 in five U.S. geographies. The ZIKV sub-search comprised a shrinking share of online media about mosquitoes over time. Net sentiment, numerical scoring of search result positivity/negativity bounded between −100 and +100, was assessed. Mean net sentiment for the general mosquitoes search was −51; -55 for ZIKV. The ZIKV search revealed more variation in weekly net sentiment with a standard deviation of 14, compared to 10 for mosquitoes. Seventy-seven percent of the weeks had a net sentiment for the mosquito search that was more positive than the ZIKV search. For the 23% of the time the ZIKV search net sentiment was more positive than the general mosquito search, there were mentions of scientific advances, such as the potential for vaccine development associated with the post. Greater emphasis on public health threats from mosquitoes may be necessary to stimulate public action on mosquito-borne illness control. This analysis serves as an illustration of the potential for online/social media analysis to inform health officials of public interest/focus, and perhaps inform effective communication campaigns to combat public health threats.